DIFFICULTIES IN IDENTIFICATION OF СOMAMONAS KERSTERSII STRAINS ISOLATED FROM INTESTINAL MICROBIOTA OF RESIDENTS OF REPUBLIC OF GUINEA AND RUSSIAN FEDERATION - E. V. Voitenkova (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
The Сomamonas genus, described in 1985, included one species — Сomamonas terrigena. At present, the Сomamonas genus includes  21 species. The ability of Comamonas to survive in environmental  objects (samples of water, soil and plants), including hospital  environment and medical equipment, allows them to be considered  as opportunistic microorganisms. The purpose of the research was to study the biological properties and antimicrobial susceptibility of  Сomamonas kerstersii strains isolated from fecal samples of healthy  people living in Saint Petersburg (Russian Federation) and the  Republic of Guinea. The study was carried out in the laboratory of  enteric infections of the St. Petersburg Pasteur Institute. 1532 fecal  samples were obtained from residents of St. Petersburg and 46  samples from residents of the Republic of Guinea. The generic and  species identification of the isolated microorganisms was carried out  using routine biochemical tests, the NEFERM test24 commercial test  system (MIKROLATEST, Erba Rus, Russia) and Vitek 2 Compact  (BioMerieux). The difficult for identification microorganisms were  studied by MALDI-TOF mass spectrometry, on a “Microflex LRF”  mass-spectrometer. Antimicrobial susceptibility was determined by  the gradient method with MICEvaluator™ (OXOID, UK) on Müller– Hinton agar (Russia). In the intestine microbiota of 1532 St.  Petersburg residents among the opportunistic microorganisms two  strains of С. kerstersii were isolated (0.13%). In a survey of 46  residents of the Republic of Guinea in 8 cases (17.4%) С. kerstersii  were isolated. The identification of C. kerstersii strains using various  methods and biochemical tests has shown different results: routine  biochemical tests allowed the strains to be assigned to the group of  non-fermenting gram-negative bacteria; NEFERM test24 kit identified all strains as С. testosteroni; VITEC 2 referred all strains to С.  testosteroni; using mass spectrometry with a coincidence ratio of  2.19–2.33, all strains were identified as С. kerstersii. It should be  taken into account that the С. kerstersii bacteria cannot be identified by the tests of NEFERM test24 kit and the GN VITEC 2 card, since  only the С. testosteroni is represented in the databases of both  methods. The taxonomic base of mass spectrometry includes  reference spectra of five species of Сomamonas from 21 known  ones, including С. kerstersii. Strains isolated from the inhabitants of  the Republic of Guinea were unsusceptible to at least one tested  antibiotic: ciprofloxacin (4 strains), tetracycline (5 strains) and  trimethoprim/sulfamethoxazole (5 strains), almost all strains being simultaneously unsusceptible to several antibio tics: ciprofloxacin  and trimethoprim/sulfamethoxazole (2 strains), tetracycline and  trimethoprim/sulfamethoxazole (2 strains), ciprofloxacin and  tetracycline (1 strain). One strain was unsusceptible to ciprofloxacin, tetracycline, and trimethoprim/sulfamethoxazole.